Challenges of turning medical education and clinical training into e-learning during the Corona epidemic - and the experience of the Faculty of Medicine at the Free University of Aleppo in the north of Syria – A theoretical study - Toukaj, Omar Ahmed (Journal of medical and pharmaceutical sciences, 2022)
After most universities and medical colleges saw evidence of the possibility of the Corona crisis continuing, and then the impossibility of continuing to postpone the study, they resorted to the (distance education) option, and one of the most prominent challenges faced by the College of Medicine at the Free University of Aleppo - like other developing countries - was the problem of switching to distance education. After in general, and how to face the difficulties and the effects resulting from the suspension of attendance on the practical and clinical aspects in particular, given the importance of practical training in the College of Medicine, which creates real fear and a logical question about the future doctors’ lack of the necessary clinical skills, as it was known - as it was training. This review aims to study the challenges posed by online education in medical education, and then what are the solutions and proposals to overcome these challenges in the light of the experiences of a number of countries (developing, developed and high-income) to benefit from the results it reached in the event of having to resort to education Telemedicine The study concluded that there is a great similarity between the challenges in low-income countries because e-learning is new in them, and the most important of these challenges is the lack of acceptance of the idea of ​​e-learning, especially at the beginning of the crisis, limited access to computers, limited infrastructure, high costs, and unfamiliarity with Some teachers and students are using e-learning. While the results in developed and high-income countries were encouraging to continue e-learning, both in terms of the mechanisms by which it was implemented, or in terms of student and teaching staff satisfaction, which calls for the conclusion of the importance of e-learning in crisis conditions in addition to the possibility of benefiting from it in some aspects, such as when Lack of teaching staff in some specializations, even after returning to traditional education face to face. However, the impact of e-learning in practical and clinical aspects still needs to be evaluated further in the future.